ANALISIS SUMBER PEMAHAMAN FALSAFAH TERAPI MUZIK PADA ABAD PERTENGAHAN ISLAM (Analysis of Philosophical Understanding Sources on Music Therapy in the Middle Ages of Islam) - Abdullah, Mohd Jailani; Sidik @ Mat Sidek, Roziah; Kamaruzaman, Azmul Fahimi; Mohamad Bohari, Firuz Akhtar (Journal of Al-Tamaddun, 2020)
Music therapy has been developed rapidly in medieval Islam from the 9th century to the 16th century AD. It has been applied as a therapeutic treatment for mental patients in hospitals and being as a medium to stimulate the memory to the Divine (zikrullah) especially for muslims mystics through al-samac concerts. It’s rapid development in both fields was the result of a deep understanding of medieval Muslim scholars on the philosophy of music therapy. The question is, what are the sources that gave them the understanding of the philosophy of music therapy? Therefore, the objective of this article is to uncover and analyze the source of understanding of the philosophy of Islamic medieval music. This study uses qualitative methodology and library research method by analyzing various primary and secondary sources. The findings of this study clearly show that the source of philosophical music therapy is derived from the civilizations of Mesopotamia, Egypt, China and Greece. Later, it was developed by scholars of Islamic civilization by making improvements in line with the Islamic paradigm.